2015
DOI: 10.14207/ejsd.2016.v5n3p285
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Framework for Ranking State and Municipal Governments on Fiscal Sustainability

Abstract: Abstract:Fiscally distressed governments tend to draw public attention only amid prominent events like bankruptcy filings, credit downgrades, and serious service cuts. Ideally, before the situation became so severe, the public would be able to quickly assess a government's financial health, both individually and relative to peers. Recognizing the challenge of consistently assessing governments' fiscal health, we developed a uniquely broad data set and proxy measures of fiscal health. For more than 10,000 state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…We use a novel proprietary dataset, GovRank, to identify distressed governments that could plausibly serve as a counterfactual to the eight state takeover events we study. GovRank is a panel of audited financial statements for more than 8000 general purpose local governments spanning 2009 to 2014 (Kaldani et al, 2016). A significant advantage of audited financial statements over the Census of Governments data is that they contain government-wide financial data inclusive of all financial resources and obligations of each government in the accrual basis of accounting (Ross et al, 2015).…”
Section: Building the Analytical Samplementioning
confidence: 99%
“…We use a novel proprietary dataset, GovRank, to identify distressed governments that could plausibly serve as a counterfactual to the eight state takeover events we study. GovRank is a panel of audited financial statements for more than 8000 general purpose local governments spanning 2009 to 2014 (Kaldani et al, 2016). A significant advantage of audited financial statements over the Census of Governments data is that they contain government-wide financial data inclusive of all financial resources and obligations of each government in the accrual basis of accounting (Ross et al, 2015).…”
Section: Building the Analytical Samplementioning
confidence: 99%
“…In addition, Bisogno et al, (2019) define this variable as 'the ability of a public sector organisation to raise sufficient revenues to cover its legally required expenditures without falling into deficit', which is in line with the concept of nonfinancial budgetary balance studied here. The asset information is also included as variables explaining financial sustainability by Kaldani et al (2016) and Gerrish and Spreen (2017). Trussel and Patrick (2018) use indicators related to debt that are similar to those in our study: debt service (our indebtedness) and debt per capita, and Robbins et al (2016) apply indicators linking debt to income and assets.…”
Section: /44mentioning
confidence: 99%
“…Kim & Ryu (2017) revealed that financial condition covers a wide dimension, so it is very complex to understand. However, it is very important to understand that financial condition and financial health are often used interchangeably (Ramsey, 2013;Kaldani et al, 2016). Kloha et al (2005) Financial condition is the most widely used terminology (Casal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%